Switching From Fear to No Fear by Different Neural Ensembles in Mouse Retrosplenial Cortex. (19th March 2019) - Wang, Guangyu; Xie, Hong; Wang, Lun; Luo, Wenhan; Wang, Yixiang; Jiang, Jun; Xiao, Chun; Xing, Feng; Guan, Ji-Song
Abstract: Fear extinction is generally considered a form of new learning that inhibits previously acquired fear memories. Here, by tracking immediate early gene expression in vivo, we found that contextual fear extinction training evoked distinct neural ensembles in mouse retrosplenial cortex (RSC). The optogenetic reactivation of these extinction-activated neurons in the RSC was sufficient to suppress a fear response, while the reactivation of conditioning-activated neurons in the same area promoted a fear response. The generation of such an extinction-memory-related neural ensemble was associated with adult neurogenesis, as abolishing newborn neurons in the adult hippocampus via X-ray irradiation eliminated both the extinction-activated neurons in the RSC and the optogenetic-reactivation-induced suppression of contextual fear memory. Therefore, switching from fear to no fear in response to the same context is modulated by the RSC through an extinction-activated neural ensemble, the generation of which might require adult neurogenesis in the hippocampus.